Penyuluhan Hipertensi dan Pelatihan Pemanfaatan Tanaman Obat untuk Mengontrol Tekanan Darah pada Masyarakat Nagrak dan Ciangsana - Kurniasari, Kurniasari; Kalumpiu, Joice Viladelvia; Herwana, Elly; Kosasih, Adrianus (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
Hypertension is one of the non-communicable diseases with a high prevalence in Indonesia. This disease can cause various complications that lead to the death of the sufferer. Consumption of medicinal plants is one of the simple ways that ordinary people can do to control blood pressure. In this activity, counseling on hypertension and training on how to recognize and process native Indonesian medicinal plants so that they can be used to control blood pressure. Activity’s evaluation is carried out using questionnaires before (pre-test) and after (post-test) counseling and evaluation of the overall implementation. The results of the Wilcoxon signed rank test showed that the post-test results were significantly higher than the pre-test (p=0.046). After the training, participants became skilled in recognizing medicinal plants that are useful for controlling blood pressure as well as understanding how to process medicinal plant parts and the amount that must be consumed.